Crowdsourcing medical emergency system using Internet of things in Bangladesh perspective - Yesmin, Romana; Hasan, Sadman Sakib (Brac University, 2019)
This thesis is submitted in partial fulfilment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2018.